Comparison of the Diagnostic Accuracy of the MSLN Gene Products, Mesothelin and Megakaryocyte Potentiating Factor, as Biomarkers for Mesothelioma in Pleural Effusions and Serum. Issue 2 (6th August 2013) - Creaney, Jenette; Sneddon, Sophie; Dick, Ian M.; Dare, Hanne; Boudville, Neil; Musk, Arthur William; Skates, Steven J.; Robinson, Bruce W. S.
Abstract : The MSLN gene products, soluble mesothelin and megakaryocyte potentiating factor (MPF), are being investigated as biomarkers for the asbestos-related cancer malignant mesothelioma (MM). Pleural fluid biomarkers of MM can be elevated when serum levels remain normal. The aim of this study was to determine if this was true for MPF and to compare levels of mesothelin. Biomarker concentrations were compared in 66 MM patients, 39 patients with other malignancies, 37 with benign disease, 18 asbestos-exposed healthy individuals, and 53 patients with chronic kidney disease. In pleural effusions, MPF and soluble mesothelin concentrations were both significantly elevated in MM patients relative to controls. No significant difference between the area under the receiver operator curve (AUC) for MPF (0.945 ± 0.02 ) and mesothelin (0.928 ± 0.03 ) when distinguishing MM from all other causes of effusion was observed. MPF and mesothelin serum concentrations were highly correlated and of equivalent diagnostic accuracy with AUCs of0.813 ± 0.04 and0.829 ± 0.03, respectively. Serum levels of both markers increased with decreasing kidney function. In conclusion, MPF is elevated in the pleural effusions of MM patients similar to that of mesothelin. Mesothelin and MPF convey equivalent diagnostic information for distinguishing MM from other diseases in pleural effusions as well as serum.